Primary high-grade urothelial carcinoma of the prostate combined with acinar adenocarcinoma: first rare case report and treatment experience summary - Hu, Ting; Liu, Yisha; Nie, Yu; Gu, Chengpeng; Wang, Guopeng; Zhang, Jinze; Zhou, Fang; Ren, Shangqing; Wang, Dong (Frontiers in Oncology, 2025)
IntroductionPrimary high-grade urothelial carcinoma of the prostate (PHUCP) combined with acinar adenocarcinoma is an extremely rare malignancy, with no previously reported cases worldwide. Primary urothelial carcinoma of the prostate (PUCP) accounts for only 1%-4% of all prostate malignancies, and its clinical manifestations often overlap with common prostatic diseases such as benign prostatic hyperplasia (BPH), leading to frequent misdiagnosis. This study presents the first documented case and summarizes the diagnostic and therapeutic approach.Case presentationA 61-year-old male patient presented with lower urinary tract symptoms and was initially diagnosed with BPH, later revised to Gleason score 10 prostate adenocarcinoma at external hospitals. Following an innovative port-free single-site robot-assisted radical prostatectomy (pf-ssRARP) at our institution, immunohistochemical analysis (CK7/CK20/GATA3 positive, prostate-specific antigen (PSA) negative) confirmed the diagnosis of PHUCP combined with acinar adenocarcinoma. Postoperatively, a surgery combined with targeted and immunotherapy regimen was initiated: leuprorelin + rezvilutamide for the acinar adenocarcinoma and disitamab vedotin + toripalimab for the urothelial carcinoma. No recurrence or metastasis was observed during the 1-year follow-up period.ConclusionThis case underscores the diagnostic challenges of prostatic urothelial carcinoma and highlights the importance of immunohistochemistry in cases with normal PSA but rapid progression. The protocol of surgery combined with targeted and immunotherapy offers a new treatment strategy for this rare malignancy. This study provides valuable insights for clinical diagnosis and management.